2006
DOI: 10.1097/01.sla.0000217608.08582.35
|View full text |Cite
|
Sign up to set email alerts
|

Postconditioning, a Series of Brief Interruptions of Early Reperfusion, Prevents Neurologic Injury After Spinal Cord Ischemia

Abstract: Postconditioning prevents neurologic injury of the spinal cord after ischemia, and the first few minutes of reperfusion are crucial to neuroprotection by postconditioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
52
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 27 publications
1
52
0
Order By: Relevance
“…It has been reported that ischemic postconditioning with 1 minute of reocclusion after 1 minute of reperfusion protects against spinal cord ischemic damage in rabbits, a larger species with a different neural structure than that of rats. 8 In studies in the heart, it appears that smaller body size (and hence, heart size) requires shorter cycles, whereas models with larger body sizes (and lower myocardial metabolic rates) require cycles of longer duration. 17 Therefore, we speculate that different animals need different strategies of reperfusion/reocclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that ischemic postconditioning with 1 minute of reocclusion after 1 minute of reperfusion protects against spinal cord ischemic damage in rabbits, a larger species with a different neural structure than that of rats. 8 In studies in the heart, it appears that smaller body size (and hence, heart size) requires shorter cycles, whereas models with larger body sizes (and lower myocardial metabolic rates) require cycles of longer duration. 17 Therefore, we speculate that different animals need different strategies of reperfusion/reocclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that ischemic postconditioning is neuroprotective, can reduce infarct size after focal brain ischemia, and can reduce neuronal injury after spinal cord ischemia. 7,8 In clinical emergencies, many accidents lead to global ischemia, such as drowning, cardiac arrest, and marked hypotension during cardiopulmonary surgery, and the brain is intrinsically more vulnerable to ischemia than other organs. 9 However, whether postconditioning has neuroprotective effects against global cerebral I/R injury is unknown.…”
mentioning
confidence: 99%
“…In addition, a clinical report has also demonstrated postconditioning induced protection to human heart during acute myocardial infarction. 9) IPoC induced protection against I/R injury has also been reported in brain, 4,10) spinal cord, 11) kidney 12) and liver. 13) Unlike preconditioning, the experimental design of postconditioning allows direct application in the clinical settings to salvage ischemic tissue.…”
mentioning
confidence: 95%
“…7) Further, several recent-reports from our laboratory 8,9) as well as from others [10][11][12] have advocated cerebro-protective role of ischemic post-conditioning. The major advantage of post-conditioning is its clinical feasibility and it has been observed to produce tissue protective effects in various clinical settings.…”
mentioning
confidence: 99%